Eigenzinnig : Roland Jooris Amédée Cortier Roger Raveel Dan Van Severen Raoul De Keyser Karel Dierickx. - Huize St.-Bonaventura, Gent (Gent : Octave de Achtste, 2011)
Jooris, Roland ; Cortier, Amédée ; Raveel, Roger ; Van Severen, Dan ; De Keyser, Raoul ; Dierickx, Karel
Eigenzinnig Roland Jooris, Huize St.-Bonaventura, Gent, van zondag 1 mei tot en met zondag 8 mei 2011
kunstcatalogus